Intracellular stability of diphtheria toxin fragment A in the presence and absence of anti-fragment A antibody. - Yamaizumi, M (1982)
The erythrocyte ghost function method was used to introduce 125I-labeled diphtheria toxin, its fragments A and B, and two labeled crossreacting material (CRM), mutant proteins CRM176 and CRM197, into cultured mouse cells. Fragment A was relatively stable in mouse cytoplasm at 37 degrees C and at least 80% was recovered from cells after 24 hr of incubation. In contrast, wild-type fragment B and A fragments from CRM176 and CRM197 were unstable and were degraded with half-lives of about 2.5 hr under similar conditions. When a rabbit anti-fragment A IgG fraction was introduced with wild-type A, the rate of degradation of A was accelerated, whereas the rates of degradation of A176 and A197 were retarded by the same antibody. In every instance the degradation rate appeared to be that of the IgG fraction itself with a half-life of about 7.5 hr.